Curriculum Reform and Value-Based Education: A Comparative Study of Social Studies and Islamic Studies Integration in Nigerian Schools - Adamu Abu Bakar Muhammad; Maryam Adam; Gaji Maiwada Abubakar; Nafisa Kabir Galadanci; Abdulkareem Ahmad Tijjani (Halaqa: Journal of Islamic Education, 2026)
The growing moral, political, and social concerns confronting contemporary Nigerian society have fueled proposals for curriculum reform focused on value-based education. Although Social Studies and Islamic Studies are both intended to enhance ethical consciousness, citizenship, and moral responsibility, they are administered concurrently rather than in a coordinated manner. This study critically investigates the philosophical, pedagogical, and structural aspects of combining Social Studies and Islamic Studies in Nigerian schools to improve coherent value formation. The research uses a qualitative comparative design to analyze national curriculum papers, engage teachers and curriculum planners in semi-structured interviews, and observe classroom practices in chosen secondary schools. The study, based on curricular integration theory and maqāṣid al-sharīʿah-informed ethical frameworks, suggests that integration can increase moral internalization, civic involvement, and social cohesiveness while maintaining disciplinary integrity. The findings show strong overlaps in value targets, fragmented educational delivery, and institutional hurdles that prevent synergy. The study presents an integrative curriculum framework built on common value domains, collaborative pedagogy, and outcome-based evaluation. It concludes that systematic integration is a strategic avenue for developing holistic education and sustained national development in pluralistic societies.